The Effect of Piper aduncum N-Hexane and Dichloromethane Leaves Extracts on Pathogenic Bacteria and Fungi. - P. M. Ridzuan; Badhrulhisham Aisyah; A. Kausar; Y. Nazifi; Osman Misbah; A.A. Azlin; A.T. Anas; Z. Syaza; Nor Iza A. Rahman; Salwani Ismail (Asian Journal of Medicine & Health Sciences, 2021)
Background : The usage of herbal medicines to cure variety illnesses caused by bacteria and fungi are increasing among Malaysians. Thus, the study of natural plants and their extracts as potential antibacterial and antifungal has been accelerated. The objective is to determine the in vitro antimicrobial effects of P. aduncum against pathogenic bacteria and fungi. Methods: Extracts of P. aduncum at different concentrations were used to evaluate the effects on bacteria and fungi. Two different solvents were used in the extraction process and the differences between the effects of the products were also compared. The zones of inhibition were observed after 24-hour incubation. The evaluation of antimicrobial and antifungal activities were performed by introducing the concentrations of the extract onto petri dishes containing newly inoculated agar plates of pathogenic bacteria and fungi. Then, the agar plates were incubated at 37°C for 24 hours. The zones of inhibition were measured to determine the antibacterial and antifungal activities. Results: Both extracts of P. aduncum (500 mg/ml) show the largest zone of inhibition compared to other concentrations. However, Staphylococcus aureus, Staphylococcus epidermidis and Candida tropicalis showed insensitive towards n-hexane extract while Bacillus subtilis is resistant towards DCM extract. Conclusion: In conclusion, the highest concentration from both solvents are the most effective antibacterial and antifungal where the most potent one is the DCM extracts of P. aduncum